2003
DOI: 10.1007/s00534-002-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalase, superoxide dismutase, and glutathione peroxidase activities in various rat tissues after carbon tetrachloride intoxication

Abstract: The results suggest that change in antioxidant enzyme activities may be relevant to the ability of the liver and other investigated organs to cope with oxidative stress during CCl4 poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
95
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(115 citation statements)
references
References 31 publications
(73 reference statements)
14
95
0
1
Order By: Relevance
“…This brief period might not be sufficient to demonstrate any rise in serum protein levels. Szymonik-Lesiuk et al (2003) have shown that CCl 4 intoxication can lead to alteration in kidney; these findings are in accordance with the present observation. In the present study, an increased frequency of glomerulosclerosis and tubulointerstitial alterations was found in rats with reduced renal mass on CCl 4 administration (Figure 4c), thereby indicating nephrotoxicity on CCl 4 administration in rats.…”
Section: Discussionsupporting
confidence: 82%
“…This brief period might not be sufficient to demonstrate any rise in serum protein levels. Szymonik-Lesiuk et al (2003) have shown that CCl 4 intoxication can lead to alteration in kidney; these findings are in accordance with the present observation. In the present study, an increased frequency of glomerulosclerosis and tubulointerstitial alterations was found in rats with reduced renal mass on CCl 4 administration (Figure 4c), thereby indicating nephrotoxicity on CCl 4 administration in rats.…”
Section: Discussionsupporting
confidence: 82%
“…SOD catalyzes the superoxide anion into oxygen and hydrogen peroxide, which are later on converted into water by CAT (39). ROS also affects the antioxidant defense mechanism by reducing the intracellular concentration of GPx and decreasing the activity of SOD and CAT (36).…”
Section: Introductionmentioning
confidence: 99%
“…Although CCl 4 is primarily metabolized in liver, its determinant effect on the brain is well documented (Boer et al, 2009). The lipid solubility of CCl 4 allows it to cross cell membranes and be deposited in different tissues such as the liver, brain and testes (Szymonik-Lesiuk et al, 2003). Free radicals have been implicated in multiple CNS disorders (Kuloglu et al, 2002) because the CNS tissue is highly sensitive to oxidative stress due to its high oxygen consumption, high iron and lipid contents, especially polyunsaturated fatty acids, and the low activity of antioxidant defenses (Carbonell and Rama, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Animal tissues are constantly coping with highly reactive species, such as superoxide anion, hydroxyl radicals, hydrogen peroxide, and other radicals generated during numerous metabolic reactions (Castillo, 1992;Hartley et al, 1999;Cabre et al, 2000;Melin et al, 2000). It is known that oxidative stress resulting from increased free radical production after CCl 4 intoxication may play a crucial role in the degenerative processes in many tissues of the body (Szymonik-Lesiuk et al, 2003). The cerebellum is a motor structure involved in posture, maintenance of balance, coordination of voluntary movement and motor learning (Alexander et al, 2012).…”
Section: Introductionmentioning
confidence: 99%